At last - St. Aubyn, Edward, 1960- (Farrar, Straus and Giroux, 2012)
Friends, relatives, and foes trickle in to pay final respects to Patrick's mother, Eleanor. An American heiress, Eleanor married into the British aristocracy, giving up the grandeur of her upbringing for "good works" freely bestowed on everyone but her own son, who finds himself questioning whether his transition to a life without parents will indeed be the liberation he had so long imagined.